Extraction of Anthocyanins from Dragon Fruit Peel Using Solvent Extraction Method - Mohammad Fathur Rohman Y.; Shariska Putri Devina; Boy Arief Fachri; Istiqomah Rahmawati; Zuhriah Mumtazah (University of Jember, 2024)
Dragon fruit skin contains 26.4587 mg/L anthocyanins. Anthocyanins have benefits such as natural coloring agents in the food sector and are used as an alternative to synthetic dyes which are of course also safer for health. The purpose of this study was to determine the effect of extraction variables (time, solvent concentration, and particle size) on the anthocyanin content of dragon fruit skin from the extraction results with the Solvent Extraction method. The definition of Solvent Extraction is the separation of materials from a solid or liquid with the help of a solvent. The extraction process starts from the agglomeration of the extract with the solvent then contact occurs between the material and the solvent so that on the flat plane of the interface of the extraction material and the solvent there is mass deposition by diffusion. The extraction process starts with 25 grams of dragon fruit peel powder with a variety of particle sizes (30, 60, and 80 mesh) then put into an Erlenmeyer tube. Then, the citric acid solution with various concentrations (0.1 M; 0.2 M; and 0.3 M) was added as much as 250 ml. After that, the Erlenmeyer was placed on a stirrer to stir for (90, 120, and 150 minutes). After that, the extraction results were filtered using filter paper to produce a filtrate. Then the filtrate was precipitated to obtain anthocyanin extract. After that, it was analyzed using the spectrophotometric method to calculate anthocyanin content. In this study, the best results were obtained at 11.439 mg/L in conditions without repetition. The optimum conditions of extraction were obtained at a particle size of 60 mesh, a time of 150 minutes, and a solvent concentration of 0.5 M citric acid.